Russian Federation : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2016)
This Selected Issues paper describes structural reform policies in Russia in the last 15 years. There is evidence of a gradual convergence of Russia's performance to that of more advanced economies, though significant gaps remain. Progress in Russia's global competitiveness index indicators during the past 10 years has been generally stronger for those indicators in which Russia's performance was comparatively weaker in 2006. The authorities' view that oil prices will be persistently low and a real exchange rate more aligned to fundamentals should serve as incentives to build a less oil-dependent growth model. Clear targets, carefully sequenced actions, appropriate accountability, and frequent monitoring could help advance reforms.